Morphological evaluation of submandibular salivary glands of white (Aerodramus fuciphagus) and black (Aerodramus maximus) edible bird's nest swiftlet - Mitin, Helen; Abdul Razak, Intan Shameha; M. I., Kamarudin; Abu Bakar @ Zakaria, Md Zuki (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
The Aerodramus fuciphagus (A. fuciphagus) and Aerodramus maximus (A.maximus) are known to use their saliva as the nest building material during breeding season. The histochemical characterizations of Edible Bird’s Nest swiftlet Aerodramus fuciphagus (A. fuciphagus) and Aerodramus maximus (A.maximus) submandibular salivary glands were studied and evaluated in 5 male and 5 female birds. The birds were humanely euthanised using 15mg/kg sodium phenobarbital. The histochemical staining used in this study were Alcian Blue-PAS, PAS, Aldehyde fuchsin-Alcian Blue and Alcian Blue at pH 1 and pH 2.5. This study demonstrated that the submandibular salivary glands were weakly sulphated mucins producing glands and acidic carboxylated mucins which are mass produced to build the nest as well as lubricating of the food ingested.